Attitudes of English Language Education Students at Ganesha University of Education toward British and American Accents - I Made Denny Andy Putra; Ni Luh Putu Eka Sulistia Dewi; I Ketut Trika Adi Ana (Jurnal Multidisiplin Sahombu, 2026)
This study aims to determine students' attitudes towards British and American accents and the factors that influence students' attitudes towards British and American accent. This study was conducted using explanatory sequential mixed method. Data collection was carried out by administering questionnaires and semi-structured interviews. Data analysis is divided into two, namely data analysis methods using descriptive statistics and data analysis techniques using typology analysis. This study found most students preffered American accent. The questionnaire results revealed that Undiksha English Language Education students preferred the American accent over the British accent because it was easier to understand and facilitated smoother communication. Several respondents preferred the British accent because it was unique, had shorter pronunciations, and sounded more elegant and formal. Interviews revealed nine factors influencing students' attitudes toward the British and American accents.